2021
DOI: 10.1111/faf.12545
|View full text |Cite
|
Sign up to set email alerts
|

Recreational angler satisfaction: What drives it?

Abstract: Satisfaction is the reward that recreational anglers receive from their experiences, and it constitutes a relevant management target. Angler satisfaction also shapes preferences for regulations, compliance with rules and general angler behaviours. Because of its central role in recreational fisheries management, it is important to understand what drives angler satisfaction. Our objective was to study the catch and non‐catch‐related determinants of recreational angler satisfaction using a standardized literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 163 publications
(306 reference statements)
5
43
1
Order By: Relevance
“…This is a typical finding that has been well established in the literature (e.g., Driver and Knopf 1976;Fedler and Ditton 1994;Ross and Loomis 2001;Arlinghaus 2006;Beardmore et al 2011). However, it has previously been found that independent of the underlying motives, most anglers derive satisfaction from the catch aspects of fishing (Arlinghaus 2006;Birdsong et al 2021). In line with this, both expected CPUE and orientation toward catching many fish and trophy fish revealed that catch-related aspects were highly relevant, in agreement with other research from the UK on the motives of anglers targeting freshwater predators (Nolan et al 2019a).…”
Section: Discussion and Management Implicationsmentioning
confidence: 52%
“…This is a typical finding that has been well established in the literature (e.g., Driver and Knopf 1976;Fedler and Ditton 1994;Ross and Loomis 2001;Arlinghaus 2006;Beardmore et al 2011). However, it has previously been found that independent of the underlying motives, most anglers derive satisfaction from the catch aspects of fishing (Arlinghaus 2006;Birdsong et al 2021). In line with this, both expected CPUE and orientation toward catching many fish and trophy fish revealed that catch-related aspects were highly relevant, in agreement with other research from the UK on the motives of anglers targeting freshwater predators (Nolan et al 2019a).…”
Section: Discussion and Management Implicationsmentioning
confidence: 52%
“…For many recreational fishers, measures of optimal fish status relate more to individual fish size and abundance (i.e. catch rate; Arlinghaus et al, 2014;Beardmore et al, 2015;Birdsong et al, 2021), rather than maximum biomass yield (Johnston et al, 2010), and the benefits of a fish stock to recreational fishers are thus usually maximised at lower fishing mortality rates than those that produce MSY (Ahrens et al, 2020;Hilborn, 2007;Radomski et al, 2001). For instance, size truncation reduces the satisfaction of those recreational fishers that prefer large pike in the catch (Arlinghaus et al, 2014(Arlinghaus et al, , 2020Beardmore et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we suggest that anglers who strongly value the environment will be more concerned with the impacts of aquatic invasive species both to their local fishing site and to the environment more broadly given that biospheric values were far stronger predictors of risk perceptions. As guiding principles in life (Rokeach 1973), values are one of the most fundamental influences on environmental behavior that remain unchanged throughout the lifespan and could be incorporated in future fisheries research to complement the large body of work focused on angler satisfaction (Birdsong et al 2021).…”
Section: Constructmentioning
confidence: 99%